Impact of donor Epstein–Barr virus serostatus on the incidence of graft-versus-host disease in patients with acute leukemia after hematopoietic stem-cell transplantation: a study from the acute leukemia and infectious diseases working parties of the European Society for blood and marrow transplantation. - Styczyński, Jan; Dreger, Peter (Journal of clinical oncology, 2016)
Purpose: We investigated the effect of Epstein-Barr virus (EBV) serostatus on the overall outcome of allogeneic hematopoietic stem-cell transplantation (allo-HSCT).Patients and MethodsThe study included 11,364 patients who underwent allogeneic peripheral-blood or bone marrow transplantation for acute leukemia between 1997 and 2012. We analyzed the impact of donor and recipient EBV serologic status on overall survival, relapse-free survival, relapse incidence, nonrelapse mortality, and incidence of graft-versus-host disease (GVHD) after allo-HSCT.ResultsPatients receiving grafts from EBV-seropositive donors had the same overall survival as patients who received grafts from EBV-seronegative donors (hazard ratio [HR], 1.05; 95% CI, 0.97 to 1.12; P = .23). Seropositive donors also had no influence on relapse-free survival (HR, 1.04; 95% CI, 0.97 to 1.11; P = 0.31), relapse incidence (HR, 1.03; 95% CI, 0.94 to 1.12; P = .58), and nonrelapse mortality (HR, 1.05; 95% CI, 0.94 to 1.17; P = .37). However, in univariate analysis, recipients receiving grafts from seropositive donors had a higher risk of chronic GVHD than those with seronegative donors (40.8% v 31.0%, respectively; P < .001; HR, 1.42; 95% CI, 1.30 to 1.56). When adjusting for confounders, higher risk was identified for both acute and chronic GVHD. In seronegative patients with seropositive donors, the HR for chronic GVHD was 1.30 (95% CI, 1.06 to 1.59; P = .039). In seropositive patients with seropositive donors, the HR was 1.24 (95% CI, 1.07 to 1.45; P = .016) for acute GVHD and 1.43 (95% CI, 1.23 to 1.67; P < .001) for chronic GVHD. Seropositive patients with seronegative donors did not have an increased risk of GVHD.ConclusionOur data suggest that donor EBV status significantly influences development of acute and chronic GVHD after allo-HSCT.
Gesehen am 20.03.2018